4th party logistics service providers and industrial cluster competitiveness: collaborative operational capabilities framework. Issue 7 (8th August 2016) - Subramanian, Nachiappan; Gunasekaran, Angappa; Papadopoulos, Thanos; Nie, Pie
Abstract : Purpose: Firms within industrial clusters are subject to challenges such as globalization, limited resources, volatility of international markets, and financial instabilities. 4th party logistics service providers (4PL) are supporting individual firms to overcome such challenges by using collaborative operational capabilities from within an industrial cluster to their enhance competitiveness. This paper focuses on China and proposes a collaborative operational capabilities framework to illustrate the role of 4PL in industrial cluster competitiveness. Design/methodology/approach: The paper follows an extensive literature review and structured interviews in two types of clusters, drawing on Resource Based View (RBV) and importance-performance matrix analysis. Findings: The paper proposes six elements (that is, synergy of logistics, expansion of industrial chain, financial ability, creativity and innovation ability, cooperation of companies and flexibility of supply chain) that comprise collaborative operational capabilities, and highlights the role of 'creativity and innovation ability' and 'supply chain flexibility' in the use of 4PL for industrial cluster competitiveness in Chinese context. Research limitations/implications: The paper focuses on China and hence it could also be tested in the developed countries' context with the support of large-scale empirical data to investigate further its usefulness and to identify other constraints. Originality/value: The study contributes to the 4PL literature in that it proposes a framework that extrapolates the importance of 4PL in industrial cluster competitiveness in China.